Adaptación de pruebas psicológicas y desarrollo de software para población limitada visual : cuestionarlo de personalidad 16 PF forma C. - Jaimes Osma, Jesús Enrique (Acta Colombiana de Psicología, 2001)
This paper shows the adaptation of the Sixteen Personality Factor Questionnaire (16 PF) Form C for people with visual impairments, and a software developed for its application, t he study worked with 43 subjects (23 men and 20 women) with visual impairments from the Blind National Institute in Bogota, Colombia. The interitem consistency coefficient Alpha was 0.3758. The procedure of content related validation involved 17 experts who assessed relevance, pertinence, and editing of the 13 modified items. The software lets the individual to answer the test alone: it provides the score profile and permits recalculate the ditlerent ype of Test Scores, (percentiles and decatypes). The profiles are per gender with the of those direct and derived scores.